2015
DOI: 10.1002/jsfa.7126
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of general proteolytic, milk clotting and antifungal activity of Ficus carica latex during fruit ripening

Abstract: Ficin forms with different casein specificities are present in different proportions during fruit ripening, which is of importance for applications in the dairy industry. The protection mechanism against insects and fungi, which relies on chitinolytic activity, is the most important in the early phases of flowering and is replaced with other strategies over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 39 publications
2
27
0
2
Order By: Relevance
“…It is well known that C. cardunculus coagulant contains two enzymes, cardosin A and cardosin B, which are similar to chymosin and pepsin in terms of casein hydrolysis [40] while ficin isolated from the latex of various Ficus species possesses certain milk coagulation properties. Interestingly, ficin represents a heterogeneous protein fraction of fig latex, which includes at least five different isoforms with different milk clotting properties and caseinolytic activities [38,41] (page 8). In order to determine the MCA/CA ratio, which is essential for a plant extract's application in cheesemaking, the caseinolytic activities of Cc, Cp and Fc was evaluated at various temperatures (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that C. cardunculus coagulant contains two enzymes, cardosin A and cardosin B, which are similar to chymosin and pepsin in terms of casein hydrolysis [40] while ficin isolated from the latex of various Ficus species possesses certain milk coagulation properties. Interestingly, ficin represents a heterogeneous protein fraction of fig latex, which includes at least five different isoforms with different milk clotting properties and caseinolytic activities [38,41] (page 8). In order to determine the MCA/CA ratio, which is essential for a plant extract's application in cheesemaking, the caseinolytic activities of Cc, Cp and Fc was evaluated at various temperatures (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Raskovic et al (2015) measured changes in enzyme activities in Ficus carica latex during fruit ripening. These findings suggested that shifts occur in the peak activities of each defense-related enzyme during fruit ripening, which are serial strategies against insects and fungi [ 59 ]. Chitinolytic activity in Ficus carica latex at the beginning of flowering was 6.5 times greater than that when the fruit was ripe.…”
Section: Discussionmentioning
confidence: 99%
“…As ripening proceeds, the skin color of the receptacle changes, providing an important source of anthocyanins [79]; sugars accumulate in the receptacle and the texture softens, constituting the edible part of the fig fruit. The receptacle is also a major tissue for latex production by laticiferous cells; latex has a protective function against insects and fungi [10], but a negative effect on fig taste.…”
Section: Introductionmentioning
confidence: 99%